2021
DOI: 10.1177/00207640211057732
|View full text |Cite
|
Sign up to set email alerts
|

Mental health and wellbeing of Indonesian medical students: A regional comparison study

Abstract: Background: Our previous research found very high levels of burnout and mental health problems among medical students across Indonesia, in line with rates in many other countries. This study further analyses the data by comparing six different regions of Indonesia to determine any differences between them on such measures and to look for possible explanations. Results: Our sample of 1,729 students reported high levels of burnout and ‘mild’ psychiatric illness across all six regions. There were however signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 11 publications
1
7
0
2
Order By: Relevance
“…Alongside a rapid increase in the number of students and scholarly output in Indonesian HE [ 11 ], the number of students claiming poor mental wellbeing has also increased. Consistent with findings in other countries [ 12 , 13 , 14 ], the mental wellbeing of Indonesian university students is compromised [ 15 ]. About a third to a half (37–53%) of undergraduate students in Indonesia reported high-stress symptoms [ 16 ], 25% experienced depression and 51% experienced anxiety [ 17 ].…”
Section: Introductionsupporting
confidence: 88%
See 1 more Smart Citation
“…Alongside a rapid increase in the number of students and scholarly output in Indonesian HE [ 11 ], the number of students claiming poor mental wellbeing has also increased. Consistent with findings in other countries [ 12 , 13 , 14 ], the mental wellbeing of Indonesian university students is compromised [ 15 ]. About a third to a half (37–53%) of undergraduate students in Indonesia reported high-stress symptoms [ 16 ], 25% experienced depression and 51% experienced anxiety [ 17 ].…”
Section: Introductionsupporting
confidence: 88%
“…In addition, high levels of loneliness have been reported [ 18 ]. Whereas the serious nature of depleted mental wellbeing among Indonesian university students has been clearly reported [ 15 , 17 , 19 ], information about the high financial cost of treatment, as well as the stigma surrounding mental health, support and treatment, is not readily available [ 20 ]. A lack of university mental health services and underutilisation of existing services is also common in non-Western countries [ 21 ], including Indonesia [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that rates of burnout in medical students vary from 52% to 95% in various countries (Pablo & Suberviola, 1998). Reports from Brazil (Castaldelli-Maia et al, 2019), Canada (Wilkes et al, 2019, 2021), England (Farrell, Kadhum et al, 2019), India (Philip et al, 2021), Indonesia (Kloping et al, 2021), Iran (Ashrafi et al, 2021), Italy (Volpe et al, 2019), Jordan (Masri et al, 2019), Morocco (Lemtiri Chelieh et al, 2019), New Zealand (Farrell, Moir et al, 2019), Nepal (Kafle et al, 2021), Nigeria (Esan et al, 2019), Paraguay (Torales et al, 2019), Portugal (Almeida et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, there has been an increase in the number of students claiming poor mental wellbeing [ 5 ]. Several studies have shown the mental wellbeing of Indonesian higher education students is lower than those in other countries.…”
Section: Introductionmentioning
confidence: 99%